Identification of pain patterns in unhappy patients after total knee arthroplasty. Issue 9 (28th September 2020) - Mathis, Dominic; Hauser, Antonia; Amsler, Felix; Hirschmann, Michael
Introduction: About 20% of patients after total knee arthroplasty (TKA) are not satisfied nor pain free. After a challenging diagnostic workup it is not unusual that revision surgery becomes necessary. There is a general consensus that knee revision surgery should only be performed when the causes of the complaints are identified. In the clinical diagnostic process the detection of pain patterns that are typical for specific pathologies is paramount. Revision surgeons in clinical practice are well aware of some pain patterns but to date there is no study dealing with detection and identification of typical pain patterns in patients with painful TKA. Hypotheses: The primary aim of this study was to precisely assess various characteristics of pain in patients after TKA qualifying for revision surgery and hence identify specific pain patterns. Secondary aim was to attribute the identified pain patterns to the underlying pathologies and implant characteristics. We hypothesised that specific pain patterns can be identified and then attributed to typical pathologies, which are being held responsible for the cause of pain. Methods: A retrospective cohort of 97 painful primary TKA patients were systematically evaluated in a specialized knee centre according to a standardised diagnostic algorithm. The end point of the clarification process results in a diagnosis which is being held responsible for the pain and states the indication for revision surgery. Within this process pain character, location, dynamics of pain and pain radiation is assessed and correlated with TKA characteristics and the underlying pathologies. Results: Most frequent pain characters were pricking/lancinating (45.7%), pinching/crushing (38.6%), dull/heavy (38.6%) and hot/searing (27.1%); 89.5% of all patients localized their knee pain anteriorly, 63.2% laterally, 57.9% medially and 5.3% posteriorly. 81.4% reported pain aggravations under strain, 48.1% on descending and 35.8% on ascending stairs, 25.6% at night. Radiation to the thigh, lower leg and spine was reported in 17.3, 13.6 and 9.9% of the patients. In 74.2% of the patients more than one underlying pathology was found; instability (52.6%), patella- (56.7%) and component-related problems (28.9%) are the most reported ones. Based on these findings nine specific pain patterns were identified including typical correlations between pain and TKA characteristics and pathologies. For example, pattern one represents pricking/lancinating, hot/searing and jumping/shooting pain, typically medially localized, aggravated in flexion and relieved by walking downhill, attributed to an instability problem of the TKA. Conclusion: The assessment of painful TKA patients involving specific pain patterns and its correlation with underlying pathologies, help to further differentiate and define the clinical picture of a painful knee after TKA. Knowing these pain patterns in patients with painful TKA enables a prediction of the cause of the pain to be made as early as possible in the diagnostic process. If the causes of the described complaints are known, a decision for a necessary therapy can also be made reliably and sustainably at an early stage before the state of pain becomes chronic.